Development and thermal management of 10 kW CW, direct diode laser source. (January 2016) - Zhu, Hongbo; Hao, Mingming; Zhang, Jianwei; Ji, Wenyu; Lin, Xingchen; Zhang, Jinsheng; Ning, Yongqiang
Abstract: We report on the development of direct diode laser source with high-power and high reliability. The laser source was realized by the polarization and wavelength combination of four diode laser stacks. When at the operating current of 122 A, the source was capable of producing 10, 120 W output while maintaining 46% electro-optical conversion efficiency. The maximum temperature on the lens was decreased from 442.2 K to 320 K by utilizing an efficient thermal dissipation structure, and the corresponding maximum von Mises stress was reduced from 75.4 MPa to 14 MPa. In addition, a reliability test demonstrated that our laser source was reliable and potential in the applications of laser cladding and heat treatment. Highlights: We developed a reliable, industrial-grade direct diode laser source with an output of 10, 120 W. The techniques of polarization and wavelength combination were used in this source. We simulated and analyzed the thermal stress of lens in this source. The temperature and von Mises stress of lens were decreased by water-cooled. A 24 h test was carried out to prove the reliability of this diode laser source.